Analisa Performance Mesin Screw Press Menggunakan Metoda Overall Equipment Effectiveness (Studi Kasus: PTPN V Sei Pagar) - Fauzul Hamdi Siregar; Anita Susilawati; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The Overall Equipment Effectiveness (OEE) is one of the methods of maintenance activities, which aim to preserve and maintain the quality of the equipment or machinery. The OEE in maintenance activities may include measuring the level of availability, level of performance, and level of quality of the machines to produce a product. This research aims to analyze the performance of machine using OEE method (case study: the machine screw press in PTPN V Sei Pagar). The research was carried out on screw press machine in the PTPN V Sei Pagar. The company is engaged in palm oil processing industry that produces crude palm oil and kernel. The research method used the Total Productive Maintenance (TPM) approach to analyze the value of OEE based on the Statistic Software of SPSS 21. Analysis result over a period of eight weeks of OEE values were obtained on a screw press,which was 47.3%. The OEE values of the screw press machine were still below the standard of OEE’s world class, which was over 85.4%. Based on analyzing of the value of six big losses that was known as the affecting factor of the low value of the OEE on the screw press machine, that was found the very significant losses on the set up and adjustment losses. The value of OEE on the set up and adjustment losses of the screw press was 45.6%. Using cause and effect diagram was obtained the root causes of the low value of OEE due to very high the schedule of stand by the machine. By using SPSS 21 software proved that each of six big losses factors have a relationship and affect the value of OEE with significant value under 0.05.Keywords : OEE, Six Big Losses, Cause and Effect Diagram, SPSS 21